Panel: Faculty Leadership - Karam, Lina; Zissis, Georges; Yao, Jason; Nelson, Jill; Jo, Minho; Sliz, Rafal; Nogueira, Michele; Watkins, Steve; Wang, Huihui (Proceedings - Frontiers in Education Conference, 2023)
This faculty leadership panel will be held jointly by the IEEE Education Society (IEEE EdSoc) and IEEE Educational Activities Board (EAB) Faculty Resources Committee (FRC). The panel intends to provide participants introductory knowledge and skills. Two moderators and four panelists will focus on discussing their various academic leadership experiences and practices. The panel will be held in an interactive way so that the participants will have enough time to ask questions or communicate with the panelists. It is expected that this joint panel may potentially help to build up networks and mentorships.